Discovery of N‑[5-(6-Chloro-3-cyano-1-methyl‑1H‑indol-2-yl)-pyridin-3-ylmethyl]-ethanesulfonamide, a Cortisol-Sparing CYP11B2 Inhibitor that Lowers Aldosterone in Human Subjects - Papillon, Julien P. N; Lou, Changgang; Singh, Alok K; Adams, Christopher M; Ksander, Gary M; Beil, Michael E; Chen, Wei; Leung-Chu, Jennifer; Fu, Fumin; Gan, Lu; Hu, Chii-Whei; Jeng, Arco Y; et al. (Journal of medicinal chemistry, 2015)
Human clinical studies conducted with LCI699 established aldosterone synthase (CYP11B2) inhibition as a promising novel mechanism to lower arterial blood pressure. However, LCI699’s low CYP11B1/CYP11B2 selectivity resulted in blunting of adrenocorticotropic hormone-stimulated cortisol secretion. This property of LCI699 prompted its development in Cushing’s disease, but limited more extensive clinical studies in hypertensive populations, and provided an impetus for the search for cortisol-sparing CYP11B2 inhibitors. This paper summarizes the discovery, pharmacokinetics, and pharmacodynamic data in preclinical species and human subjects of the selective CYP11B2 inhibitor 8.